Antimicrobial Stewardship in Acute Care Centres: A Survey of 68 Hospitals in Quebec. Issue 3 (2008) - Nault, Vincent; Beaudoin, Mathieu; Thirion, Daniel JG; Gosselin, Michel; Cossette, Benoit; Valiquette, Louis
Abstract : BACKGROUND: Antimicrobial stewardship programs (ASPs) and quantitative monitoring of antimicrobial use are required to ensure that antimicrobials are used appropriately in the acute care setting, and have the potential to reduce costs and limit the spread of antimicrobial-resistant organisms and Clostridium difficil e. Currently, it is not known what proportion of Quebec hospitals have an ASP and/or monitor antimicrobial use. OBJECTIVES: To determine what proportion of Quebec hospitals have an ASP, and what is the nature of such a program. METHODS: A detailed questionnaire was sent to the pharmacy directors of all acute care hospitals in the province of Quebec. Information was collected on antimicrobial surveillance; antimicrobial stewardship and resource allocation to these areas were assessed. RESULTS: Questionnaires were completed for 68 of 81 (84%) hospitals contacted. ASPs were identified at 50 (74%) hospitals, but only 20 (29%) of hospitals had a quantitative antimicrobial surveillance program (QASP) in 2006. Academic centres (P=0.03) and hospitals with over 200 beds (P=0.02) were more likely to have a QASP. Even among hospitals with an ASP, 18% had less than one full-time pharmacist for a QASP. CONCLUSIONS: Over one-quarter of Quebec hospitals do not have an ASP, and few hospitals in Quebec are currently evaluating their use of antimicrobials on a quantitative basis. In some cases, the lack of a QASP may be due to the allocation of insufficient pharmaceutical resources to antimicrobial stewardship (ie, less than one full-time pharmacist).